Analysis of the Effect of Segmentation and Targeting on Sales - Tina Muhardika Handayani; Brilian Moktar (Jurnal Manajemen Bisnis Eka Prasetya, 2023)
This study aims to determine the effect of Segmentation on Sales at PT. Mega Anugrah Mandiri, to determine the effect of Target on Sales at PT. Mega Anugrah Mandiri, to determine the effect of Segmentation and Target on Sales at PT. Mega Anugrah Mandiri. The research methodology used is descriptive quantitative method. The type of data used in this study is quantitative data, namely data obtained in the form of numbers or numbers. Sources of data in the form of primary data and secondary data. Primary data obtained from the results of distributing questionnaires to respondents, secondary data obtained from data and literature relating to the problems discussed. The research population that will be used in the study are all consumers who made purchases at the company during the 2020 period as many as 1,039 consumers. By using the Slovin formula with an error rate of 10%, the number of samples obtained is 50 respondents The results of this study are supported by the value of R square (R2) = 0.138, meaning that the Sales variable can be explained by the Segmentation and Target variables of 13.8% while the remaining 86.2% is influenced by other factors originating from outside this research model. such as product quality, consumer behavior, business communication, service, satisfaction, and other variables.